Teacher’s Perspective Toward Students’ Foreign Language Anxiety In Efl Classroom - Nur Hikmah1; Nurul Faradillah; Isumarni .; Fenny Hasanuddin (La Ogi : English Language Journal, 2023)
This research looks at teachers' perspectives or suppositions on language anxiety, particularly in the matter of how they have seen and managed students’ language anxiety in their actual teaching practices. In reference to the characteristic features of student anxiety reported in the relevant literature This research additionally talks about the teachers' perspectives as far as whether there are any gaps or inconsistencies with the students' affective needs in language classroom. In this sense, this research can be considered as an endeavor to give some elective bits of knowledge into language anxiety from a different point of view. Similar to the interview study by Young (1992) concerning the points of view of language specialists (Krashen, Omagio, Terrell, and Rardin) on language anxiety, this research likewise utilizes a qualitative in-depth interview format to examine the two experienced EFL teachers' viewpoints on the circumstance. As the interview result show, a considerable lot of the records from the participants appear to for the most part validate the discoveries offered by past research on language anxiety, however there are likewise a few contrasts or gaps between the teachers' and students' point of view on the part of tension in the EFL classroom context